THE EFFICIENCY ANALYSIS OF ISLAMIC RURAL BANKS (BPRS) IN EAST JAVA USING DATA ENVELOPMENT ANALYSIS (DEA) FOR 2012-2018 PERIOD - Nafilatul Khusnah; Irham Zaki; Lina Nugraha Rani (Universitas Airlangga, 2020)
Efficiency is needed by Islamic Rural Bank (BPRS)to facing rivalry in the banking sector. Efficiency can show the performance of BPRS and make BPRS more productive. This study measures the efficiency of Islamic Rural Banks (BPRS) in East Jawa using data envelopment analysis (DEA). DEA is a non-parametric and deterministic methodology for determining relative efficiency. This study used the intermediation approach and output orientation to measure the efficiency of BPRS. Inputs in this study are deposits, labor, and fixed assets. Outputs in this study are financing and other income. The result shows that the inefficiency exists in the BPRS in East Java. From 21 BPRS, which were used as a sample, 17 BPRS are not efficient technically. The inefficiency of BPRS causes BPRS still can not manage its inputs optimally to producing maximum output. To achieve an efficient level, BPRS needs to increase its output and reduce its input.Keywords: Islamic Rural Banks (BPRS), Efficiency, Performance, Data Envelopment Analysis (DEA)REFFERENCE Ali, M. M., & Ascarya. (2010). Analisis Efisiensi Baitul Maal Wat Tamwil dengan pendekatan two stage Data Envelopment Analysis (Studi kasus kantor cabang BMT MMU dan BMT UGT Sidogiri). TAZKIA: Islamic Finance & Business Review, 5(2), 110–125.Ascarya, & Yumanita, D. (2006). Analisis efisiensi perbankan syariah di Indonesia dengan Data Envelopment Analysis. TAZKIA Islamic Finance and Business Review, 1(2), 1–27.Ascarya, & Yumanita, D. (2008). Comparing the efficiency of islamic banks in Malaysia and Indonesia. Buletin Ekonomi Moneter Dan Perbankan, 11(2), 95-119.Ascarya, Yumanita, D., Achsani, N. A., & Rokhimah, G. S. (2010). Measuring the efficiency of islamic banks in Indonesia and Malaysia using parametric and nonparametric approaches. 3rd International Conference on Islamic Banking and Finance. SBP-IRTI. Jakarta, Indonesia.Iqbal, zamir & Mirakhor, Abbas. (2012). The Islamic financial system. In an introduction to islamic finance: theory and practice (pp. 113-136). Singapore: John Wiley & Sons.Khumbakar, Subal C. & Lovell, C.A. knox. (2012). Stochastic frontier analysis, United Kingdom: Cambridge University Press.Nurhandini. (2006). Analisis efisiensi industri perbankan di Indonesia dengan metode non parametrik Data Envelopment Analysis. Skripsi tidak diterbitkan. Depok: Fakultas Ekonomi dan Bisnis Universitas Indonesia.Prasetyo, Muhammad Budi. (2007). Perbandingan pengukuran efisiensi perbankan syariah di Indonesia dengan perbankan syariah di Malaysia pada tahun 2003-2006 dengan metode DEA. Skripsi tidak diterbitkan. Depok: Fakultas Ekonomi dan Bisnis Universitas Indonesia.https://bps.go.id https://www.ojk.go.id/id/kanal/perbankan/data-dan-statistik/statistik-perbankan-indonesia/default.aspx https://www.ojk.go.id/id/kanal/perbankan/regulasi/peraturan-ojk/Default.aspx https://www.ojk.go.id/waspada-investasi/id/regulasi/Pages/Undang-Undang-Nomor-21-Tahun-2008-Tentang-Perbankan-Syariah.aspx